The Effect of the Mysterious Physics Learning Model Based on Fun Learning on the Physics Learning Outcomes - Pertiwi, Pertiwi; Harnipa, Harnipa; Hasan, Nurhikmah; Fatmawati, Titin (Universitas Muhammadiyah Makassar, 2022)
This study aims to identify whether the mysterious physics learning model based on fun learning has an effect on the physics learning outcomes of the students. This study was a pre-experimental study with one group joining the pretest-posttest research design. This study was carried out at SMPN 2 Barombong in November 2021. The population was all the students of class IX, while the sample was class IX.B which was determined by a simple random sampling technique. Data analysis used Wilcoxon signed-rank test statistic. The results showed that there was a positive and significant influence of the mysterious physics learning model based on fun learning on the physics learning outcomes of students at SMPN 2 Barombong. The results of the student questionnaire also showed interest in learning physics. They considered it as a more challenging physics learning project which made them more enthusiastic about it. The conclusion obtained is that the implementation of mysterious physics learning based on fun learning is effective in increasing students' learning outcomes in physics learning.